Fragmentation in the euro overnight unsecured money market - Carlos Garcia-de-Andoain; Peter Hoffmann; Simone Manganelli (European Central Bank (ECB), 2014)
This paper examines the degree of fragmentation in the Euro overnight unsecured money market during the period June 2008 – August 2013 using interbank loans constructed from payments data. After controlling for cross-country differences in bank risk, we document several episodes of significant market fragmentation. While non-standard measures such as the provision of long-term liquidity were successful in reducing tensions, considerable signs of market fragmentation remained at the end of the sample period.
Keywords: G1; E5; 330; Financial integration; monetary policy implementation; money markets; sovereign debt crisis